2021
DOI: 10.1071/an20545
|View full text |Cite
|
Sign up to set email alerts
|

Herbaceous legumes provide several options for increasing beef cattle productivity in eastern Indonesia

Abstract: Context Increasing demand for livestock products in developing countries provides opportunities for smallholder farmers to increase and diversify their income through increased livestock production. However, livestock production in these systems is often limited by inadequate animal nutrition, and farmers need ways to increase the availability and quality of livestock feed without compromising yields of food crops or increasing the area of land planted to forages. Aim Using eastern Indonesia as a case study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Previous authors have reported that increasing multiple cropping in suitable areas could increase these global crop-cultivable areas by 87-395 million hectares [92,98]. Herbaceous plants, also known as herbs or vegetables, are perennial, annual, or biennial, depending on the region in which they are grown and their ability or lack thereof to survive in winter, drought, wet, or dry seasons [99]. In addition to multi-layered crops, herbaceous cropping has worldwide acceptance because it is a sustainable source of nutrients for soil fertility [100].…”
Section: Subsidized Fertilizer Use and Crop Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous authors have reported that increasing multiple cropping in suitable areas could increase these global crop-cultivable areas by 87-395 million hectares [92,98]. Herbaceous plants, also known as herbs or vegetables, are perennial, annual, or biennial, depending on the region in which they are grown and their ability or lack thereof to survive in winter, drought, wet, or dry seasons [99]. In addition to multi-layered crops, herbaceous cropping has worldwide acceptance because it is a sustainable source of nutrients for soil fertility [100].…”
Section: Subsidized Fertilizer Use and Crop Productionmentioning
confidence: 99%
“…In addition to multi-layered crops, herbaceous cropping has worldwide acceptance because it is a sustainable source of nutrients for soil fertility [100]. It can solve soil erosion, leaching, and evaporation problems [99]. Further, herbaceous crops supply food for people and livestock in all seasons, provided that irrigation is applied where needed [49,99].…”
Section: Subsidized Fertilizer Use and Crop Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dry climate with long dry season (8-9 months) in East Nusa Tenggara has significant effects on the growth and productivity of forage supply for the ruminant livestock, especially cattle in the region. The negative effects including high calf mortality of Bali Cattle in West Timor (30 to 50%) [1,2], long calving interval (2-3 year) of Sumba Ongole Cattle in Sumba Island, and low annual average live daily weight gain of cattle (0.2 to 0.3 kg/head/day) [3,4] in the whole province (Bali Cattle, Sumba Ongole Cattle as well as other local and introduced breeds) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A. Improved animal nutrition: Hoste et al, 2012;Sousa et al, 2015;Améndola et al, 2016;Sordillo, 2016;Nwafor et al, 2017;Mangwe et al, 2019;Mayberry et al, 2020B. Increased animal welfare: García-Cruz et al, 2013Cuartas et al, 2014;Lerner et al, 2015;Pezo et al, 2018 C. Positive indirect effects on human health: Harvey et al, 2006;Moreno and Pulido, 2010;Rivera et al, 2013;Montoya-Flores et al, 2020Synergy Khan et al, 2008Descheemaeker et al, 2010;Peters et al, 2012;Cheruíyot et al, 2020;Wan et al, 2020;Zahoor et al, 2021…”
Section: Animal Healthmentioning
confidence: 99%